The citizen challenging the state: Islamic State and the recruitment of foreign fighters - Al-Dayel, Nadia (2020)
This thesis critically examines the role of the Islamic State’s foreign fighter. It argues that the projection in propaganda of reflexive, foreign fighters and migrants operates as a recruitment device. This evidence challenges current assumptions of foreign fighters, who are often tautologically confined to “religious ideological” motivations in a group pre-determined as religiously ideological. It reveals that the Islamic State is acutely aware of its salience as a competitive political actor, attempting to provoke a sense of political agency through an articulation of the fragile conditions in the citizen-state relationship.